Pengaruh Return On Aset, Current Ratio, Debt To Equity Ratio dan Earning Per Share Terhadap Harga Saham : (Studi Empiris Pada Perusahaan Sub Sektor Makanan dan Minuman di Bursa Efek Indonesia Periode 2019-2023) - Serina Indah Fitriani; Retno Fuji Oktaviani (Pajak dan Manajemen Keuangan, 2024)
This study aims to determine the effect of Return On Asset, Current Ratio, Debt To Equity Ratio and Earning Per Share on Stock Prices in Food and Beverage Sector Companies on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. In this study, a quantitative research method was used with population and samples in Food and Beverage Sector Companies on the Indonesia Stock Exchange for the 2019-2023 period. The companies that are the object of this research are 23 companies that are determined through certain criteria. The analysis methods in this study consist of, Classical Assumption Test, Correlation Coefficient Analysis Test, Multiple Linear Regression Analysis Test, Determination Analysis Test (R2), t-Test and Test F. Meanwhile, the data analysis method used is multiple linear regression with a significance value of 0.05 using Statical Product and Service Solution (SPSS) Version 25.0. The results of this study show that Return On Asset has a positive and significant effect on the Stock Price, the Current Ratio does not have a significant effect on the Stock Price, the Debt to Equity Ratio has a positive effect on the Stock Price and Earning Per Share has a negative and significant effect on the Stock Price.